Emotional States Related to Sexual Offending Versus Violent Offending Using a Schema Therapy Perspective - Keulen-de Vos, Marije (International journal of offender therapy and comparative criminology, 2024)
The aim of this study was to examine the emotional states preceding and during sexual and violent offenses in a Dutch sample of male forensic inpatients. Moreover, the predictive impact of these emotional states on institutional violence in the first year of mandated care was examined using an incident scheme. Observer-ratings of emotional states by 103 male offenders and 97 sex offenders were examined using Mann-Whitney U tests. Using hierarchical multiple regression analyses, the predictive relationship between crime-related emotional states and incidents was examined. Sexual and violent crimes were equally preceded by painful emotions, primarily feelings of abandonment. During violent crimes, a state of bully and attack was dominant whereas sexual crimes were also characterized by self-aggrandizement and manipulation. These emotional states were not predictive for institutional violence. This study emphasizes the importance of emotional states in offending behavior and usefulness of schema therapy’s crime theory.